2022
DOI: 10.3389/fnut.2022.982369
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to mediterranean diet and the risk of differentiated thyroid cancer in a European cohort: The EPIC study

Abstract: BackgroundThe Mediterranean diet (MD) has been proposed as a healthy diet with a potential to lower the incidence of several types of cancer, but there is no data regarding thyroid cancer (TC). We investigated the association between MD adherence, and its components, and the differentiated TC risk within the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort.MethodsOver 450,000 men and women from nine European countries were followed up for a mean of 14.1 years, during which 712 differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Furthermore, the few studies conducted with the aim of exploring the association between dietary habits and the risk for TC highlighted that while dietary patterns of fruits, vegetables, seafood, and milk and dairy products led to a reduced risk of TC [10,181,182], the Western dietary pattern-starchy foods, sweets, and products rich in salt and fat-showed a significantly positive association with TC risk [10,183]. In contrast, the EPIC study, conducted on over 450,000 men and women from nine European countries for a total of 712 cases of differentiated TC identified over a 14.1-year follow-up, did not find a significant association between high adherence to a Mediterranean diet and decreased risk of differentiated TC [184].…”
Section: Diet: Enemy or Friend Of The Gut Microbiota?mentioning
confidence: 80%
“…Furthermore, the few studies conducted with the aim of exploring the association between dietary habits and the risk for TC highlighted that while dietary patterns of fruits, vegetables, seafood, and milk and dairy products led to a reduced risk of TC [10,181,182], the Western dietary pattern-starchy foods, sweets, and products rich in salt and fat-showed a significantly positive association with TC risk [10,183]. In contrast, the EPIC study, conducted on over 450,000 men and women from nine European countries for a total of 712 cases of differentiated TC identified over a 14.1-year follow-up, did not find a significant association between high adherence to a Mediterranean diet and decreased risk of differentiated TC [184].…”
Section: Diet: Enemy or Friend Of The Gut Microbiota?mentioning
confidence: 80%
“…Using the relative Mediterranean diet score (rMED score) and adjusted relative Mediterranean diet score (arMED score), they assessed how well participants adhered to the Mediterranean diet. The results showed that high adherence to the Mediterranean diet was not associated with the development of differentiated thyroid carcinoma [ 19 ].…”
Section: Discussionmentioning
confidence: 99%